Post a New Question

algebra

posted by .

I need to know if I am doing this problem right when sustitution method.
y+2x=3
y+2x=-4
y+2x=3 -1(y+2x=3)-y-2x=-4
now add the two equation
y-2x=3
-y-2x-4
the answer would be -4y=7
then divided -4=7 answer 1.75
I no that there is more to this answer I am just stuck and not sure if this is right are not.

  • algebra -

    You are not doing substitution.

    y = 3 - 2x
    y + 2x = -4

    Substitute 3 - 2x for y in second equation and solve for x. Insert that value into the first equation and solve for y. Check by inserting both values into the second equation.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question